Anti-dyskinetic efficacy of 5-HT3 receptor antagonist in the hemi-parkinsonian rat model. (June 2019) - Aboulghasemi, Nazanin; Hadipour Jahromy, Mahsa; Ghasemi, Amir
Abstract: Parkinson's disease is a progressive debilitative neurodegenerative disease characterised mostly with bradykinesia, tremor, catatonia, drooping posture, unsteady gate and unstable steps. Levodopa has been proven to be among the most effective and acceptable treatment that can reconstitute dopamine in Parkinson's disease. However, there is a relation between levodopa long term administration and dyskinesia. Regarding the effectiveness of ondansetron in Parkinson's disease, we planned to test its effect on levodopa-induced dyskinesia (LID). In this study, Parkinsonism was induced in 40 adult male rats using 6-OHDA injection into the striatum via stereotaxic surgery. After 2 weeks, all animals tested for Parkinson's disease using apomorphine rotation test. Then, animals with positive symptoms for Parkinsonism divided into 4 equal groups, the first group treated with levodopa 50 mg/kg i.p, the second group received only distilled water, the third and forth groups treated with levodopa 50 mg/kg i.p plus two different doses of ondansetron (0.04 and 0.08 mg/kg i.p) for 3 weeks. Animals tested for dyskinesia using AIMs and rotarod tests at specific days and a week after discontinuation of ondansetron. Evaluations of AIMs test showed significant changes in dyskinetic movements and reduction in scores in groups treating with ondansetron when compared with the first group. Upon discontinuations of ondansetron in the last two groups, AIMs scores significantly increased. While in rotarod test, ondansetron had no additional benefit when added to levodopa in motor coordination of animals. Findings of this study suggest that co administration of ondansetron with levodopa is effective in attenuating dyskinesia.